2017
DOI: 10.1177/0194599817742852
|View full text |Cite
|
Sign up to set email alerts
|

Positive Margins by Oropharyngeal Subsite in Transoral Robotic Surgery for T1/T2 Squamous Cell Carcinoma

Abstract: Objective To compare positive margin rates between the 2 most common subsites of oropharyngeal transoral robotic surgery (TORS), the base of tongue (BOT) and the tonsil, as well as identify preoperative imaging characteristics that predispose toward positive margins. Study Design Case series with chart review. Setting Tertiary care referral center. Subjects and Methods We compared the final and intraoperative positive margin rate between TORS resections for tonsil and BOT oropharyngeal squamous cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 20 publications
1
25
5
Order By: Relevance
“…Persky et al in a single-institution study of 140 patients, found that PMRs were significantly higher at the BOT (19.6%) as compared to the tonsil (4.5%) and that procedures at the BOT were six times as likely to result in positive margins as compared to tonsil on multivariable analysis. 25 In contrast, we found PMRs of 15.7% and 19.4% in the tonsil and BOT, respectively, and found that this was not significant in multivariable analysis. Persky et al only controlled for HPV status and T classification in their analysis, which was also limited to a single institution.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Persky et al in a single-institution study of 140 patients, found that PMRs were significantly higher at the BOT (19.6%) as compared to the tonsil (4.5%) and that procedures at the BOT were six times as likely to result in positive margins as compared to tonsil on multivariable analysis. 25 In contrast, we found PMRs of 15.7% and 19.4% in the tonsil and BOT, respectively, and found that this was not significant in multivariable analysis. Persky et al only controlled for HPV status and T classification in their analysis, which was also limited to a single institution.…”
Section: Discussioncontrasting
confidence: 66%
“…8,23 Two single-institution studies, by Moore et al and Persky et al, reported rates of 2% and 10%, respectively, for T1 and T2 tumors. 24,25 These rates are lower than the PMRs of academic facilities in this study, even when limited to low-classification tumors (13.9%). The disparity between the PMR demonstrated here and those of smaller studies indicates that publication bias may be influencing the PMR reported in the literature and that the actual PMR of TORS nationwide in academic facilities is closer to 15%, in contrast to the lower rates previously reported.…”
Section: Discussioncontrasting
confidence: 55%
“…However, while no survival advantage is seen in tonsil primaries with TORS, tonsil primaries had lower rates of positive margins with TORS in both HPV+ and HPV− disease. TORS was not demonstrated to have survival benefit for tonsil primaries, but it may have a separate benefit of reducing the positive margin rate, which is associated with lower rates of trimodal therapy 40 . Intuitively, TORS would be expected to reduce positive margins in subsites at more difficult locations, such as the BoT.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 While avoiding functional deficits from the traditional external approaches, TORS can reduce the need for adjuvant therapy after surgery or can use surgery as a single-technique therapy while preserving oncologic outcomes, particularly when the negative margin is achieved by TORS. 2,3,5,[16][17][18] Despite these advantages, there is still a risk of obtaining an insecure surgical margin (ie, positive margin involvement by the tumor or a close margin of ,1 mm between the tumor and the margin) in TORS, which necessitates adjuvant therapies, even in early T1 and T2 tumors. 3,19 Because oncologic outcomes in such cases are similar to those with chemoradiation alone, 3 it is important to preselect patients who are expected to have an insecure surgical margin to avoid unnecessary dual treatment.…”
mentioning
confidence: 99%
“…2,3,5,[16][17][18] Despite these advantages, there is still a risk of obtaining an insecure surgical margin (ie, positive margin involvement by the tumor or a close margin of ,1 mm between the tumor and the margin) in TORS, which necessitates adjuvant therapies, even in early T1 and T2 tumors. 3,19 Because oncologic outcomes in such cases are similar to those with chemoradiation alone, 3 it is important to preselect patients who are expected to have an insecure surgical margin to avoid unnecessary dual treatment. However, no published study has evaluated the preoperative MR imaging characteristics that can predict the surgical margin after TORS.…”
mentioning
confidence: 99%